Broken Blossoms, or, The yellow man and the girl - Griffith, D. W. (David Wark), 1875-1948; Gish, Lillian, 1893-1993; D.W. Griffith, Inc.; Cinetel Films ([United States] : D.W. Griffith, 1919)
A fifteen-year-old street urchin who longs to escape her miserable existence. Emotionally scarred by the torment and neglect of her abusive father, the girl collapses outside the shop of the lonely and disillusioned 'yellow man'. As he tenderly nurtures her back to health, an unspoken romance flowers between them, awakening in each of them feelings of love.
Lillian Gish, Richard Barthelmess, Donald Crisp, Arthur Howard, Edward Pell, George Beranger, Norman Selby.
Cinematographer, G.W. Bitzer.
Silent, with English intertitles and musical accompaniment.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Chinese -- England; Abused children -- England -- London; Interracial friendship -- England -- London; Boxers (Sports) -- England -- London; Runaways (Fictitious characters); Street children -- England -- London -- Drama; Buddhist priests -- England -- London -- Drama; Suicide; Limehouse (London, England); Silent films; Romance films; Feature films; Internet videos; Streaming video